3 twin pairs share joy selected to enter UMP - Nor Salwana, Mohammad Idris (2021)
PEKAN, 9 October 2021 – Three twin pairs shared their joy after being selected to continue their studies during the registration of new students for the 2021/2022 Academic Session at Universiti Malaysia Pahang (UMP).